Hubungan Kebiasaan Konsumsi Makanan Cepat Saji Dengan Kejadian Penyakit Jantung Koroner Pada Pasien Rawat JalanDi RSUD Dr. Moewardi - Widyan Aisya, Rizki, Dr. Listiana Dharmawati S., M.Si, Dewi Pertiwi Dyah K, S.Gz., M.Gizi (2015)
Introduction: Coronary heart disease is one of diseases that requires special attention. Coronary heart disease is the leading cause of death in Indonesia, ranked first with 11.06% mortality. Coronary heart disease is caused by the process of atherosclerosis which is started from accumulation of cholesterol. One of factors that affects coronary heart disease is fast food consumption, which contains high fat, high-energy, high sodium, and low fiber. Purpose: This research aimed to understand the relationship between fast food consumption and coronary heart disease in outpatients of Dr. Moewardi Hospital. Research method: This research was an observational research with cross-sectional design. Sampling method used consecutive sampling. The subjects were 37 patients of coronary heart disease, aged 40-65 years old. Fast food consumption data were collected through interview using questionnaire and food-frequency questionnaire. Coronary heart disease data were obtained from patients' medical record. This research used statistical tests of Fisher's Exact. Results: Among patients who often consumed fast food, 76% of them had coronary heart disease. Meanwhile, those who rarely consumed fast food, 66,7% of them did not have coronary heart disease. There was a correlation between fast food consumption and coronary heart disease (p = 0,027). Conclusion: There was a relationship between fast food consumption and coronary heart disease in outpatients of Dr. Moewardi Hospital.